The The Effect of Beauty Influencer Trust on Brand Credibility, Advertising Credibility, Corporate Credibility and Purchase Intention of Local Skincare Products - Pawestriningrum, Wening; Roostika, Ratna (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2022)
This study aims to examine the effect of beauty influencer trust on brand credibility, advertising credibility, corporate credibility, and purchase intention for local skincare products. The type of sampling used is purposive sampling with a total of 243 respondents in Indonesia. The analytical method used is the Structural Equation Modeling (SEM) using AMOS (Analysis of Moment Structure) 24 software. This study finds that beauty influencer trust has a positive and significant effect on brand credibility and advertising credibility, while beauty influencer trust has an effect but not significant on corporate credibility. Advertising credibility has a positive and significant effect on brand credibility and corporate credibility. Brand credibility has a positive and significant effect on corporate credibility. Corporate credibility has a positive and significant effect on purchase intention for local skincare products.